Design considerations for the synthesis of polymer coated iron oxide nanoparticles for stem cell labelling and tracking using MRI. (7th October 2015) - Barrow, Michael; Taylor, Arthur; Murray, Patricia; Rosseinsky, Matthew J.; Adams, Dave J.
<x xml:space="preserve">Abstract</x> This tutorial review provides an introduction to the design, polymer selection and synthesis strategies that can be used to develop biocompatible polymer coatings for iron oxide nanoparticles as MRI contrast agents for stem cell tracking.